Sub-optimal temperatures lead to altered expression of stress-related genes and increased ‘Candidatus Liberibacter solanacearum’ accumulation in potato psyllid - Fisher, Tonja W.; Munyaneza, Joseph E.; Brown, Judith K. (Frontiers in Insect Science, 2024)
The potato psyllid Bactericera cockerelli is the insect vector of the fastidious bacterium 'Candidatus Liberibacter solanacearum'. This bacterium infects B. cockerelli and is associated with zebra chip disease of potato and vein greening of tomato tubers and/or fruits, respectively, making them unmarketable. Temperature influences the initiation and progression of zebra chip disease symptom development in infected potato leaves and tubers, and during seasonal transition from moderate to high temperatures, psyllid dispersal-migration is triggered and host plants suitable for reproduction become less available. Illumina RNA-Seq analysis was used to characterize relative gene expression for 'Ca. L. solanacearum'-infected and -uninfected adult psyllids reared at different temperatures. Quantitative-PCR (qPCR) was used to determine 'Ca. L. solanacearum' genome copy number in psyllids reared at previously reported permissible and non-permissible temperatures 18°C, 24°C, and 30°C. The relative gene expression was variable at the different temperatures, with those reared at 18°C and 30°C exhibiting greater-fold increased expression of psyllid encoded, stress-related and 'Ca. L. solanacearum'-invasion-related proteins. Based on results of qPCR 'Ca. L. solanacearum' concentration was significantly lower in psyllids reared at 18°C and 30°C, compared 24°C.